PELUANG DAN TANTANGAN GLOBALISASI PROFESI BIMBINGAN DAN KONSELING - MUHAMMAD SURYA (DIMENSI PENDIDIKAN, 2005)
The Rapid Growth of science and technology in global area makes the space and time be unlimited. the relationship among people is more intensive, deeeper, and more rapid than before. this condition gives more chances and challenges for counceling and guidance profession. This opportunity is that we can give counseling trough cyercounseling, multicultural counseling, spiritual counseling and holistic approach. the capability and adaptability of the conselor in coling technology become more and more chalenging.Keyword : Commnication Technology, education, counceling and guidance profession, globalization